183 Effect of fermentation temperature on in vitro digestibility of a finishing diet. (29th July 2019) - Stotz, Miranda K; Mejia-Turcios, Sebastian E; Osorio, Andrea M; Espinoza, Nadira; Urso, Philip M; Kondratovich, Lucas; Carvalho, Luis; Douglas, Michael; Sarturi, Jhones O; Henry, Darren D; Crossland, Whitney
Abstract: Heat stress (HS) has been indicated to increase ruminal temperature, increase digestibility, and reduce ruminal pH of steers fed high concentrate diets. However, it is unclear if this effect is the result of greater fermentation rate, slower passage rate, or a combination. The effect of ruminal incubation temperature on substrate digestibility and rate of fermentation were evaluated. Four cannulated British-crossbreed steers (BW = 520 kg ± 30 kg) consuming an 87% (DM) concentrate diet were utilized as rumen fluid donors in a randomized complete block design with two incubation treatments (CON=39°C and HS=42°C). Within block, duplicate 125 mL serum bottles containing 200 mg of dietary substrate were inoculated with a 2:1 buffer:ruminal fluid mixture and incubated for 24 h to measure total gas production, fermentation rate, fermentation lag, pH, and ammonia-N concentration. In vitro organic matter digestibility (IVOMD) was measured separately in 100 mL centrifuge tubes. Data were analyzed using the MIXED procedure of SAS using the fixed effect of treatment and random effect of rumen fluid donor (block). There was no treatment effect on total gas production (P = 0.92) or fermentation rate (P = 0.11); however, HS began fermenting substrate sooner than CON (P < 0.005). There was a significant effect of treatment on IVOMD where HS was greater compared to CON (79.3 vs. 70.4%; P = 0.05). Final pH and relative pH change were not different (P ≥ 0.25) likely due to buffering capacity of the in vitro technique Ammonia-N concentration was greater for HS than CON (7.92 vs. 5.33 mM; P < 0.05) and may indicate a temperature effect on ruminal nitrogen availability.In conclusion, it does not appear that incubating at a greater temperature affected the fermentation rate but likely induced a change in fermentation kinetics, which may have contributed to the greater overall IVOMD